ESTIMASI KECEPATAN REAKSI ELEKTROLISIS BERDASARKAN ENERGI LISTRIK DARI SUMBER ENERGI TERBARUKAN DENGAN ESTIMATOR EXTREME LEARNING MACHINE - I Putu Eka Suartana (2023)
Indonesia has enormous potential to develop new and renewable energy (EBT) because it is rich in sustainable natural resources such as water. Water can be used as a driving force for generators from hydropower plants and can also produce hydrogen to be used as a source of heat and electricity. Hydrogen is a source that can replace materials containing hydrocarbons. Rapid technological developments in this era allow machine learning technology to be utilized to estimate the speed of hydrogen production through the water electrolysis process, while also being able to utilize IoT technology to retrieve the required data. The algorithm used to build machine learning models is Extreme Learning Machine because data processing is relatively fast and the results obtained are also accurate. The data needed to build an estimation model, such as light intensity, temperature, humidity, voltage, current, power, and production volume of hydrogen are obtained using telemetry techniques from installed sensors in order to obtain data in real time and accurately. The model development process uses a data division of 30% for test data, 70% for training data and uses a hidden neuron parameter of 40, initializes random weights between -1 to 1, and uses the binary sigmoid activation function so that the RMSE value is 23.29. MAE is 17,061, and R2 is 0,995.